New Zealand GPS velocity field: 1995–2013. Issue 1 (2nd January 2016) - Beavan, John; Wallace, Laura M; Palmer, Neville; Denys, Paul; Ellis, Susan; Fournier, Nico; Hreinsdottir, Sigrun; Pearson, Christopher; Denham, Mike
ABSTRACT: We collate nearly two decades of campaign GPS data gathered at over 900 sites throughout New Zealand to release a New Zealand nationwide GPS velocity field. The data span the entire North and South islands of New Zealand with a typical spacing of 10–20 km and a denser network (c. 2–8 km spacing) in the Wellington region, central Taupo Volcanic Zone and parts of the Arthur's Pass area. The dataset provides the most comprehensive-to-date view of crustal deformation within the Australia–Pacific plate boundary zone in the New Zealand region. We discuss the data acquisition, processing and derivation of the velocities and uncertainties. We also undertake corrections for earthquake displacements to obtain a velocity field that is largely representative of interseismic deformation between 1995 and 2013.